Trends in Studies on Islamic Education Pedagogy: A Bibliometric Analysis with Implications for Character Education - Ni'mah, Zulfatun; Ariati, Chelsi; Suparman (Jurnal Pendidikan Islam, 2023)
Purpose – Despite the increasing significance of character education within the context of Islamic education, there is a discernible gap in scholarly discussions on this subject. This study aims to address this void by offering a bibliometric and bibliographical review concerning character education via Islamic pedagogy. Design/methods/approach – Employing a bibliometric analysis approach, this research scrutinized 117 documents extracted from the Scopus database, spanning 2007 to 2023. The analytical tools employed include performance, co-citation, co-word, and co-authorship metrics, facilitated through VOSviewer and PoP software. Findings – The investigation highlighted a moderate uptick in publications about Islamic education from 2007 to 2023. However, citation trends within Islamic education studies fluctuated between 2007 and 2023. This review also identified the pivotal documents, nations, authors, sources, and affiliations that have substantially impacted the growth trajectory of Islamic education research. Research implications – The insights derived from this study underscore the potential of Islamic education in fostering positive attitudinal shifts in students. As character education strives to mold virtuous habits, Islamic education serves as a conduit by instilling Islamic values, thereby facilitating the cultivation of commendable character traits by rectifying detrimental behaviors and mindsets.